52 Drug therapy for delirium in terminally ill adults: a cochrane systematic review. Issue 3 (1st September 2018) - Finucane, A; Jones, L; Leurent, B; Sampson, E; Stone, P; Tookman, A; Candy, B
Abstract : Introduction: Delirium is a complex neuropsychiatric syndrome common in palliative care occurring in up to 88% of patients in the weeks or hours preceding death. Our Cochrane review on drug therapy for delirium in 2012 identified one trial (Candy et al. 2012). New trials have been conducted and an updated review is now recognised as a Cochrane priority. Aim: To evaluate the evidence from randomised controlled trials (RCTs) examining the effectiveness and safety of drug therapies to treat delirium in adults with a terminal illness. Methods: We searched for RCTs comparing any drug treatment with any other treatment for delirium in terminally ill adults. Primary outcomes included delirium symptoms at 24 hours and between 24–48 hours; and adverse events. Risk of bias assessment was conducted; we assessed overall quality of evidence using GRADE. Results: We retrieved 9431 citations. Four studies were included in the final review. All trials were vulnerable to bias most commonly due to small sample size or incomplete outcome data. Figures 1 and 2 illustrate the mean difference between trial arms at 24 hours and between 24–48 hours respectively. Three studies reported adverse events revealing mixed results. Conclusion: This review identified four trials. It found low quality evidence examining the impact of drug therapy on delirium symptoms and adverse events in terminally ill adults. Results for each comparison were based on single studies. Undertaking trials on delirium in this patient group is methodologically complex. Only one study compared drug therapy with placebo. This limited our ability to answer our review questions. Reference: . Candy B, Jackson KC, Jones L, Leurent B, Tookman A, King M. Drug therapy for delirium in terminally ill adult patients. Cochrane Database of Systematic Reviews2012;(11). Art. No. CD004770. doi:10.1002/14651858.CD004770.pub2